Potensi dan Tantangan Pengembangan Sektor Unggulan di Kalimantan Barat - Achmad, Dinarjad (Fakultas Ekonomi dan Bisnis, UNTAN, 2016)
The primary objective of this study was to analyze the potential and challenges of superior sectordevelopment in West Kalimantan. Superior sectors here interpreted as a sector that producesgoods that can be exported. Descriptive method and time series data for 7 years (2007- 2013) wasused as the tools and materials to perform the analysis.The results showed that the based on ofnatural resources (land, water area and the river, fill the earth) and geography, West Kalimantanhave a greater potential for superior sector development, but there are several challenges to thedevelopment potential of the superior sector, including: (1) resource human (HR) is still weak.(2) Infrastructure (electricity, gas and water supply, road and port export) are limited. (3)Marketing and networking is still weak